A process for the deterpenation of essential oils by extraction/adsorption/desorption using supercritical carbon dioxide - Eskinazi, Orli A. (Thesis (Ph.D.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
The main purpose of this study was to establish a supercritical-fluid-aided process in order to enhance the quality of essential-oils products through the removal of the monoterpene (MT) hydrocarbons. The example oil chosen for this study among the hundreds of essential oils is origanum oil (Origanum Munituflorum). A new process arrangement constituted by a dense-CO2 extraction coupled with continuous adsorption/desorption process has been developed, and is suggested for the fractionation and successful deterpenation of this essential oil. During the different forms of operations and procedures implemented, the non-monoterpene (NMT) cut having the essential odor and properties of the origanum oil, was intended to be separated from the unstable MT fraction of the oil. Based on the experimental results, enhanced fractionation of the oil is obtained via adsorption on activated carbon at 40C/7.5 MPa and desorption at 40C with step-wise pressure increase method: first at 8.0 MPa to recover the MT components and then, at 14.5 MPa to collect the NMT constituents. This process scheme, in which the mixing cell situated before the adsorber acts as a phase separation chamber, is more successful in deterpenating origanum oil since the mixing cell adds an extra degree of flexibility to the system through providing an additional separation between the MT and NMT hydrocarbons. Furthermore, compared to silanized silica gel, activated carbon was found to be a more promising adsorbent in fractionating and producing an origanum-oil product almost free of its MT constituents.
Keywords: Supercritical fluids.; Carbon dioxide.; Extraction (Chemistry); Adsorption.